Enhanced Recovery of Airborne T(3) Coliphage and Pasteurella pestis Bacteriophage by Means of a Presampling Humidification Technique - Hatch, M. T. (1969)
This paper reports a series of experiments in which two methods of collecting airborne bacteriophage particles were compared. A standard aerosol sampler, the AGI-30, was evaluated for its competence in measuring the content of bacteriophage aerosols. It was used alone or with a prewetting or humidification device (humidifier bulb) to recover T(3) coliphage and Pasteurella pestis bacteriophage particles from aerosols maintained at 21 C and varied relative humidity. Collection of bacteriophage particles via the humidifier bulb altered both the initial recovery level and the apparent biological decay. Sampling airborne bacteriophage particles by the AGI-30 alone yielded data that apparently underestimated the maximal number of potentially viable particles within the aerosol, sometimes by as much as 3 logs.